Distortion Product Otoacoustic Emissions (DPOAEs) and Auditory Brainstem Response (ABR) Desctiption of Low Birth Weight Babies at RSUP H. Adam Malik Medan - Sara Yosephine Aruan (Pre Cure, 2014)
Aim: To know Distortion Product Otoacoustic Emissions (DPOAEs) and Auditory Brainstem Response (ABR) Values in LBW infant at H. Adam Malik General Hospital Medan.Method: A descriptive case-study was conducted in 32 LBW infants who meet the inclusion criteria. Data collection was done through hearing assessment with Distortion Product Otoacoustic Emissions (DPOAEs) and Auditory Brainstem Response (ABR).Result: From 32 LBW infants (64 ears), eight babies (25%) presented alteration in the Distortion Product Otoacoustic Emissions (DPOAEs) and Auditory Brainstem Response (ABR) test. There is a significant association between gender and ABR result, but there is no significant association between other variables and DPOAEs nor ABR result.Conclusion and Recommendation: DPOAEs and ABR can be used as an early detection tool of hearing loss in LBW infant, even though this study found no significant association in most of the variables, which may be due to the small sample size.Keywords : DPOAEs, ABR, Low Birth Weight Infant, Hearing Loss.